If Gordon Allport was right, the Likert-type personality scales must be very poor descriptors of personality: he was right - Toomela, Aaro (Frontiers in Psychology, 2025)
Gordon Allport suggested that personality has several characteristics: it is inherently inconsistent and contradictory, it is situation-dependent, where situational determinants of personality traits are crucial in structured scenarios, while internal determinants prevail in unstructured situations. Additionally, personality develops not only through maturation, and personality traits cannot be quantitatively expressed as fixed amounts along a continuum of a specific trait. Moreover, “common traits” or general personality dispositions act as useful approximations rather than true personality characteristics. Current theories, particularly the Five-Factor Theory (FFT), challenge all characteristics proposed by Allport. This study provides evidence from two distinct analyses—the reexamination of data from a previous study (N = 870) and a replication study (N = 1,423)—which evaluate the response patterns of individuals using the widely accepted Revised Neuroticism, Extraversion, Openness Personality Inventory, NEO-PI-R. The findings support all of Allport’s claims. First, it shows that only a subset of NEO-PI-R items are truly transcontextual, while the rest contain situational information. Two indices measuring the consistency of responses, namely the Consistency Index (CI) and the Decisiveness Index (DI), were developed. Second, it was noted that the level of inconsistent and indecisive responses was significantly high. Third, it was found that the consistency and decisiveness of responses were systematically and reliably linked to the presence or absence of situational information in the items and the predominant type of word meaning structure that reflects the level of psychological development. These correlations confirm that inconsistency and indecisiveness do not stem from random or careless responding styles. Consequently, an analysis of the most dubious evidence against the FFT, specifically the NEO-PI-R is the most unlikely test to refute FFT. Furthermore, the results of the current studies suggest that summary scores derived from all questionnaires and inventories utilizing Likert-type response formats may be significantly misleading; the consistency of response patterns must be empirically validated before interpreting summary scores.